2006
DOI: 10.2215/cjn.00010505
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Bicarbonate and Death in Hemodialysis Patients

Abstract: The optimal acid-base status for survival in maintenance hemodialysis (MHD) patients remains controversial. According to recent reports, acidosis is associated with improved survival in MHD patients. It was hypothesized that this inverse association is due to a confounding effect of the malnutrition-inflammation complex syndrome (MICS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
89
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(99 citation statements)
references
References 49 publications
(18 reference statements)
8
89
1
1
Order By: Relevance
“…Both low (<17 mEq/l) and high (>23 mEq/l) bicarbonate levels were associated with increased death risk [11]. Data from the DOPPS study reported similar results.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Both low (<17 mEq/l) and high (>23 mEq/l) bicarbonate levels were associated with increased death risk [11]. Data from the DOPPS study reported similar results.…”
Section: Discussionmentioning
confidence: 89%
“…The relationship between acidosis and mortality in dialysis has been investigated in a large cohort of chronic HD patients [11]. Both low (<17 mEq/l) and high (>23 mEq/l) bicarbonate levels were associated with increased death risk [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of all-cause mortality with serum bicarbonate was U shaped, with higher serum bicarbonate level also being associated with worse prognosis in CKD patients [13,16]. The nonlinear (U shaped) association of serum bicarbonate level with gait speed and quadriceps peak torque was also observed in the general population 50 years or older [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that a serum bicarbonate concentration lower than 22 mmol/l is associated with an increased risk of total death in dialysis [13,14] and nondialysis CKD patients [15,16]. The Kidney Disease Improving Global Outcomes (KDIGO) suggests that oral bicarbonate supplementation should be given to maintain serum bicarbonate within the normal range in CKD patients with serum bicarbonate <22 mmol/l [17].…”
Section: Introductionmentioning
confidence: 99%